Vitamin B12 status among anaemic adolescents - Surana, Amita; Tilwani, Sandeep; Patel, Shefali; Prajapati, Hiren; Prasad, Rajeev (International Journal Of Community Medicine And Public Health, 2017)
Background: Nutritional anaemia are common health problems. Most studies are done regarding iron deficiency anaemias. There are limited data regarding vitamin B12 deficiency anaemia especially in adolescents. Aims and objectives of the study were to find the prevalence of vitamin B12 deficiency among anaemic adolescents and to study various socio-demographic factors and hematological parameters associated with vitamin B12 deficiency. Methods: Cross sectional hospital based observational study of 211 adolescents (10 -18 year) with anaemia. Socio demographic characteristics like age, sex, education of mother & patient, socio- economic class, dietary history were noted for each patient. CBC including RBC indices and serum estimation of vitamin B12 level were done for each patient. Results: Anaemia was seen in 46.6% of adolescents. Vitamin B12 deficiency was seen in 49.76%. Vitamin B12 deficiency was significantly associated with male gender (p=0.032) and vegetarians (p=0.047). Moderate to severe degree of anaemia (p=0.016), macrocytosis (p= 0.000) and thrombocytopenia (p=0.007) was more observed in vitamin B12 deficient patients as compared to vitamin B12 non deficient groups. Statistically significant fall in mean haemoglobin level and increase in mean MCV values were seen with decreasing serum vitamin B12 level. Conclusions: Among anemic male and vegetarian adolescents vitamin B12 deficiency is a significant health problem. Hematological findings in peripheral blood are more associated with severe degree of vitamin B12 deficiency. Vitamin B12 supplementation along with IFA should be addressed through national programmes.